Pengaruh Tingkat Pendidikan, Pertumbuhan Ekonomi, dan Kepadatan Penduduk Terhadap Kualitas Hidup di Aceh - Rika Pertiwi; Asnidar Asnidar; Nurlaila Hanum; Puti Andiny; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine and analyze the Level of Education, Economic Growth, and Population Density on Quality of Life in Aceh, using a descriptive-quantitative approach in the form of time series data, for 5 years in the form of secondary data selected from the total of Aceh Province. The model used in this study is a multiple linear regression analysis model (Multiple Linear Regression) based on the OLS (Ordinary Least Square) method. Simultaneously, the F test shows that the three independent variables together have a significant effect on quality of life, with a calculated F value = 85.495, sig. = 0.000, and F table = 2.70. The coefficient of determination shows a value of R Square = 0.728, which means that 72.8% of the variation in quality of life can be explained by education level, economic growth and population density, while the rest is influenced by other variables outside the model.